Rheological characterization of human follicular fluid under shear and extensional stress conditions - Muto, Masakazu; Kikuchi, Keigo; Yoshino, Tatsuya; Muraoka, Ayako; Iwata, Shuichi; Nakamura, Masanori; Osuka, Satoko; Tamano, Shinji (Frontiers in Physics, 2023)
The rheology of human follicular fluid has been empirically evinced to be related to the reproductive health status of individuals, which supports its use as an indicator for improving the success rates of in vitro fertilization. However, there is a dearth of studies investigating the viscoelastic properties of human follicular fluid. Moreover, a comprehensive elucidation of the rheological properties of complex fluids necessitates the assessment of data regarding both shear and extensional viscosities. Nonetheless, to the best of our knowledge, the extant literature does not include reports on the behavior of follicular fluid under extensional conditions. Consequently, this study aimed to analyze the shear and extensional viscosities of human follicular fluid. Primarily, the impact of oocytes on the rheology of follicular fluid was evaluated by measuring the shear viscosity of this fluid using a high-resolution coaxial cylinder viscometer. The shear viscosity of follicular fluid exhibited marked differences depending on the presence or absence of oocytes. Subsequently, a measurement system that enables the handling of minute quantities of body fluid was developed to determine the extensional viscosity of follicular fluid, which contains albumin. A comparison of the acquired follicular fluid data with that of the protein solution containing albumin demonstrated that the follicular fluid alone displayed extensional behavior, whereas the protein solution did not. Therefore, it can be inferred that the protein solution is not its sole determinant, as other constituents of the fluid, such as peptides and cumulus cells, may determine its rheological properties. This observation was not attained through the conventional technique consisting in shear viscosity measurements.